2022
DOI: 10.3389/fbioe.2022.909653
|View full text |Cite
|
Sign up to set email alerts
|

Deep Convolutional Generative Adversarial Network-Based EMG Data Enhancement for Hand Motion Classification

Abstract: The acquisition of bio-signal from the human body requires a strict experimental setup and ethical approvements, which leads to limited data for the training of classifiers in the era of big data. It will change the situation if synthetic data can be generated based on real data. This article proposes such a kind of multiple channel electromyography (EMG) data enhancement method using a deep convolutional generative adversarial network (DCGAN). The generation procedure is as follows: First, the multiple channe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…The GAN-based model is capable of discovering the structured patterns of the references and extrapolating the underlying data distribution characteristics during the adversarial learning process [34]. For example, Chen et al [35] tested and evaluated the performance of the deep convolutional generative adversarial network (DCGAN) on sEMG-based data enhancement, and their results indicated that the extrapolated data is able to augment the diversity of the original data. Fahimi et al [36] The continuous estimation of muscle forces (F ) and joint 153 kinematics(θ) from multi-channel sEMG can be denoted as 154 the time-series generation problem.…”
Section: Takedownmentioning
confidence: 99%
“…The GAN-based model is capable of discovering the structured patterns of the references and extrapolating the underlying data distribution characteristics during the adversarial learning process [34]. For example, Chen et al [35] tested and evaluated the performance of the deep convolutional generative adversarial network (DCGAN) on sEMG-based data enhancement, and their results indicated that the extrapolated data is able to augment the diversity of the original data. Fahimi et al [36] The continuous estimation of muscle forces (F ) and joint 153 kinematics(θ) from multi-channel sEMG can be denoted as 154 the time-series generation problem.…”
Section: Takedownmentioning
confidence: 99%